Microbiological quality and physicochemical characteristics of commercially produced fish balls as affected by the handling practices of selected wet markets in Iloilo province. - Resol, Angelica Compas
Public retail markets and supermarkets currently offer a variety of traditional minced fish products and surimi-based products. These products include fish balls, squid balls, native fish sausages, fish burgers, and surimi analogs. However, consuming these products entail high risk when proper storage conditions are not appled. This study aims to determine the quality of commercially produced fish balls as affected by the handling practices of the selected wet market vendors in Iloilo. Based on a survey, wet market vendors store fish balls at -4 to -10°C and some store at 30 to 35°C. Fish ball samples from selected wet markets were subjected to microbiological and physicochemical characterization to further assess the quality and safety of the product. The results of the microbiological and physicochemical tests when subjected to independent sample t-test showed a significant difference in APC values, pH, TMA, and Aw, this is from among samples and storage temperature. The mean Aerobic Plate Count (APC) of fish balls ranged from 2.7 x 105 to 6.60 x 106 CFU/g, highest is from the sample obtained at ambient conditions. A significant difference also exists between samples stored at two storage conditions. These values, however, are within the acceptable limit for commercially processed fish balls (ICMSF, 1986). The total coliform (MPN/g) density ranges from 240 to > 1100 MPN/g and samples at ambient conditions exhibited the highest count. The values have exceeded the acceptable limit for coliform. E. coli was also detected to be present in all samples. The noted pH (4.26-5.14) and water activity (0.94 to 0.96) values of the fish balls were favorable for the growth of the aforementioned microorganisms. The TMA content ranged from 0.0044 to 0.0057 mg TMA/100g. Whereas, the TMA and pH of the prepared fish balls in the laboratory were o.0077 mg TMA/100g at pH of 5.74. The TMA value of of the experimental sample was lower than the sample prepared with fish. Indicating that the commercially produced fish balls have a minimal amount of fish in the formulation. The changes in pH and TMA are due to biochemical reactions. Part of the recommendation is to store the fish balls at freezing conditions coupled with good handling practices to minimize contamination and spoilage. A similar study to be conducted to have a conclusive data to be used for future policymaking for training and education purposes.